2019
DOI: 10.1016/j.sjbs.2019.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The clinical efficacy study of treatment to Chiari malformation type I with syringomyelia under the minimally invasive surgery of resection of Submeningeal cerebellar Tonsillar Herniation and reconstruction of Cisterna magna

Abstract: PurposeDiscuss the clinical efficacy of treatment to Chiari malformation type I with syringomyelia under the minimally invasive surgery of resection of Submeningeal Cerebellar Tonsillar Herniation and reconstruction of Cisterna magna.Methods130 Chiari malformation type I with syringomyelia patients, divided into treatment group, literature group and control group, were collected to be treated under the monitoring of ultrasound in the surgery.Results6 months after operation, the lesions were decreased or disapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Studies have confirmed that DCM is related to mutation of lamin A (27). In this study, trimetazidine combined with perindopril will be applied to treat DCM rats to study its effect on the levels of NT-proBNP, AT1Rs and lamin A in rats (27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 96%
“…Studies have confirmed that DCM is related to mutation of lamin A (27). In this study, trimetazidine combined with perindopril will be applied to treat DCM rats to study its effect on the levels of NT-proBNP, AT1Rs and lamin A in rats (27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 96%
“…In the cosmetics industry, it is currently being used as facial masks or ointments and also in food products, accompanied with other components to treat skin disease as well as help in activation of blood circulation [3]. Presently, the replacement of synthetic antioxidant with naturally occurring antioxidant is increasing due to the side effects associated with synthetic antioxidant such as increased risk of cancer [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the observation group, the expression level of CRP after treatment was significantly lower than that before treatment (P< 0.05), which may be because the antibacterial effect of antibiotics reduced patients' inflammations, weakened the infiltration of inflammatory cells and reduced the expression level of CRP. This indicates that CRP may be a potential diagnostic indicator for the efficacy of severe pneumonia (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 93%